The TRAINING FOR CHILDREN’S MOTOR DEVELOPMENT AT TPA AL-MUBASYIR DESA DIBAL, KECAMATAN NGEMPLAK, KABUPATEN BOYOLALI, CENTRAL JAVA. - Yudi Wibowo; Alma Fikri Setya Nugraha; Indah Ayu Puji Lestari; Suryaningtyas Widyastuti; Toriqot Armada Muslimin (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2022)
Abstract : Practicing motor skills is important for children, given that childhood is a golden period in child development. One technique in training children's motor skills is to provide guidance or physical exercises that are in accordance with the portion of children's physical abilities. This activity aims to improve motor skills in children through viewing animation movie, coloring pictures, and leisurely strolling for children. The activities carried out showed the attitudes and behavior of children at TPA (Taman Pendidikan Al-Quran) Al-Mubasyir to be better than before, children became more creative, thorough, responsive to the surrounding environment, and enthusiastic in participating in learning. Keywords: motor, training, children